Regioselective Glycosylation Strategies for the Synthesis of Group Ia and Ib Streptococcus Related Glycans Enable Elucidating Unique Conformations of the Capsular Polysaccharides. Issue 71 (4th November 2019) - Del Bino, Linda; Calloni, Ilaria; Oldrini, Davide; Raso, Maria Michelina; Cuffaro, Rossella; Ardá, Ana; Codée, Jeroen D. C.; Jiménez‐Barbero, Jesús; Adamo, Roberto
Abstract: Group B Streptococcus serotypes Ia and Ib capsular polysaccharides are key targets for vaccine development. In spite of their immunospecifity these polysaccharides share high structural similarity. Both are composed of the same monosaccharide residues and differ only in the connection of the Neu5Acα2‐3Gal side chain to the GlcNAc unit, which is a β1‐4 linkage in serotype Ia and a β1‐3 linkage in serotype Ib. The development of efficient regioselective routes for GlcNAcβ1‐3[Glcβ1‐4]Gal synthons is described, which give access to different group B Streptococcus (GBS) Ia and Ib repeating unit frameshifts. These glycans were used to probe the conformation and molecular dynamics of the two polysaccharides, highlighting the different presentation of the protruding Neu5Acα2‐3Gal moieties on the polysaccharide backbones and a higher flexibility of Ib polymer relative to Ia, which can impact epitope exposure. Abstract : Glycosylation : A panel of GBS serotype Ia and Ib fragments was prepared by combined regioselective‐stereoselective approaches and used to unravel polysaccharide conformations responsible for immune specificity.